Validity and Practicality of The Salt Hydrolysis Electronic Module Based on Structured Inquiry with Interconnection of Three Levels of Chemicals Representation. Issue 1 (February 2021) - Rachmawati, T.; Azhar, M.; Aini, S.; Azra, F.
Abstract: Salt hydrolysis is one of the chemical's material with the associated aqueous reaction in solution. The material is difficult to understand for students. Based on interviews, the learning process has not been interconnected by three levels of chemicals representation. The purpose of the research to decide on the validity and practicality of the salt hydrolysis electronic module based on structured inquiry with the interconnection of three levels of chemicals representation. The method of research was used by Researched and Development of Plomp model. The research instruments are used by sheets validation and sheets practicality. The electronic module was validated by 4 experts. The practicality of the electronic module was checked by 2 chemistry teachers and 60 students at two High Schools in Padang City. Validity and Practicality were analyzed by utilizing Cohen's Kappa Statistic. The outcomes of validation showed that the electronic module had an almost perfect strength of agreement with a Kappa was 0.87. The practicality level had substantial strength of agreement with a Kappa was 0.80 for the student's reaction and also almost perfect strength of agreement with a Kappa was 0.85 for the teacher's reaction. Therefore, the result electronic module of salt hydrolysis can be used as a good alternative for teaching-learning chemistry in high school.